Faktor Risiko Preeklampsia di Puskemas Dupak Surabaya: Studi Kasus Kontrol - Elga Caecaria Grahardika Andani; Muhammad Alamsyah Aziz; Johanes Cornelius Mose (EMBRIO: Jurnal Kebidanan, 2022)
Preeclampsia causes maternal death around 30-40% and tends to increase when accompanied by other organ complications. Preeclampsia is the first target to reduce maternal mortality because screening and prevention can be done. This research aims to analyze the risk factors for the incidence of preeclampsia. This research design is case control using primary data via google form. The research subjects were mothers who had given birth at Dupak Public Health Center Surabaya. Sampling was based on total sampling and simple random sampling technique that met the inclusion and exclusion criterias, each group consisted of 75 peoples. The analysis used was logistic regression and chi square. The results showed multiple pregnancies (AOR 3.89; 95% CI 0.714-21.186), family history of preeclampsia (AOR 5.19; 95% CI 1.287-20.959), previous history of preeclampsia (AOR 7.56; 95% CI 1.999-28.601), obesity (AOR 5.05; 95% CI 1.651-15.470) and chronic hypertension (AOR 5.12; 95% CI 1.294-20.312). The conclusion of this research is the previous history of preeclampsia is the strong risk factors of preeclampsia. Comprehensive antenatal care services and strict supervision of pregnant women with high risk can prevent serious complications for both mother and baby.